46.4k views
4 votes
Let f(x) = x2 + 6 and g(x) = x + 8x . Find ( g o f)(­ -7)

User Magne Land
by
4.7k points

1 Answer

3 votes

Answer:
(gof)(-7) =495

Explanation:

Given the functions f(x) and g(x), to find
(gof)(x) you need to substitute
x=f(x)=x^2 + 6 into the function g(x):


(gof)(x) = ( x^2 + 6)+ 8( x^2 + 6)\\\\(gof)(x)=x^2 + 6+ 8x^2 + 48\\\\(gof)(x)=9x^2 + 54

Now, to find
(gof)(-7) you must substitute
x=-7 into
(gof)(x), then you get:


(gof)(-7) = 9(-7)^2 + 54\\\\(gof)(-7) =9(49)+54\\\\(gof)(-7) =441+54\\\\(gof)(-7) =495

User Mickeal
by
5.1k points